Desert locust (Schistocerca gregaria Forskal) and its management: A review - Shambhu Katel; Honey Raj Mandal; Pooja Neupane; Sandipa Timsina; Pratima Pokhrel; Amrit Katuwal; Sudeep Subedi; Jiban Shrestha; Kabita Kumari Shah (Future Science, 2021)
The desert locust, Schistocerca gregaria (Forskal) (Orthoptera: Acrididae), is the world’s most dangerous and destructive migratory pest. It is a highly voracious and polyphagous insect. Its swarms can migrate hundreds of kilometers per day and invade areas covering millions of square kilometers, causing significant and widespread crop losses. In this review, we synthesize published research and reports on the life cycle, behavior, phases of desert locust along with its damage and management. Elements of locust management include population monitoring and population prediction. However, there are difficulties involved with estimating locust populations because locust swarms are highly mobile. Control techniques for managing locust swarms include cultural control (digging, burning), baiting (scattering locust food impregnated with insecticides), dusting with insecticide, and spraying liquid insecticides (chemical or biological) using ultra-low volume (ULV) application. Effective management strategy relies on improved knowledge of pest biology, more efficient monitoring and control techniques.